Plasma total and unacylated ghrelin predict 5-year changes in insulin resistance. Issue 5 (October 2016) - Barazzoni, R.; Gortan Cappellari, G.; Semolic, A.; Ius, M.; Mamolo, L.; Dore, F.; Giacca, M.; Zanetti, M.; Vinci, P.; Guarnieri, G.
Summary: Background & aims: Ghrelin is a gastric hormone circulating in acylated (AG) and unacylated (UG) forms, and higher plasma total ghrelin (TG) and UG may be cross-sectionally associated with lower insulin resistance in metabolic syndrome patients. The potential value of ghrelin forms in predicting insulin resistance and its time-related changes in community-based population cohorts remains unknown. Methods: We measured TG, AG and calculated UG (TG-AG) in 716 individuals from the North-East-Italy MoMa study (age: 55 ± 9 years, BMI: 29 ± 5 kg/m 2, M/F:349/367) to test the hypothesis that circulating TG and UG, but not AG are negatively associated with insulin resistance (HOMA). We further hypothesized that baseline TG and UG negatively predict 5-year HOMA changes in a 350-individual subgroup. Results: Baseline TG and UG were associated negatively with HOMA after adjusting for gender and body mass index (BMI). Baseline gender- and BMI-adjusted TG and UG were also negatively associated with HOMA at 5-year follow-up (n = 350), and changes in TG and UG were negatively associated with changes in HOMA (P < 0.05) after adjustment for anthropometric and metabolic confounders. No statistically significant correlations were observed between AG and baseline or 5-year HOMA. Conclusions: In a North-East Italy community-based population cohort, plasma TG and UG but not AG are negatively associated with HOMA. TG and UG and their changes also independently predict 5-year HOMA changes. TG and UG are therefore novel potential modulators of insulin resistance and may contribute to predict its time-related changes in humans.